The Integration of Islamic Family Law into Muslim Community Education in Japan: Socio-Cultural Dynamics in a Minority Context - Hasanah, Siti Mu’awanatul; Inayati, Isna Nurul; Ismail, Adawiyah Binti; Ulum, Mohammad Samsul; Kawakip, Akhmad Nurul; Marno, Marno; Hidayatullah, Achmad Diny; Fauziyah, Ulil (Nurani, 2025)
This study investigates the dynamics of integrating Islamic Family Law (Fiqh al-Usrah) into Muslim community education within minority contexts in contemporary Japan. Positioned in the interdisciplinary intersection of Islamic Education Studies and Islamic Legal Studies, it explores how legal and ethical principles of Islamic family life are transmitted amid public misconceptions of Islam, linguistic and cultural barriers, and differing levels of individual religious commitment. Using a socio-legal qualitative design with thematic analytical techniques, the research draws on primary data obtained through interviews, observations, and documentation of Muslim community activities, complemented by secondary scholarly  sources. Fieldwork was conducted in Tokyo and Ibaraki between July and August 2024, involving Japanese converts, migrant Muslim families, and mosque administrators. Thematic analysis reveals two dominant patterns: first, families who experience positive religious transformation through strong community engagement; and second, those whose Islamic identity weakens due to secular environments and cultural pressures. The integration process is supported by individual agency, the active role of mosques and Muslim organizations, and culturally embedded religious expression, including arts-based initiatives. Conversely, limited access to formal Islamic education and the socio-cultural  dominance of the non-Muslim majority remain persistent challenges. This study contributes to scholarly discourse on the contextual integration of Islamic law and education in minority contexts. It underscores the importance of systematic, community-based strategies to strengthen Islamic family identity and enhance Muslim minorities' constructive participation in Japanese society.